2015
DOI: 10.1111/ecc.12282
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following neoadjuvant cisplatin-based chemotherapy for bladder cancer in elderly compared with younger patients

Abstract: Bladder cancer is a disease of the elderly. Older patients might potentially be undertreated due to assumptions about benefit versus risk. Our objective was to determine outcomes in older patients receiving neoadjuvant chemotherapy for muscle-invasive bladder cancer (MIBC). We hypothesised that appropriately selected elderly patients (≥70 years) with MIBC could have similar clinical outcomes, and be safely treated, with standard neoadjuvant chemotherapy prior to definitive cystectomy or radiotherapy. We utilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…A single-institution case series demonstrated similar rates of eligibility for definitive local therapy following cisplatin-based NAC. Additionally, it reported similar clinical outcomes including pathologic CR, overall survival, and relapse-free survival at 3 years in patients aged ≥70 years versus younger patients with MIBC 42. A recent study of tolerability and efficacy of cisplatin-based combination chemotherapy in metastatic disease based on data from eight Phase II and III clinical trials with a total of 543 patients demonstrated no significant differences in the frequency of renal failure (grade 3–4), febrile neutropenia, or treatment-related death or median survival (12.1 months versus 12.8 months; P =0.91) for patients older and younger than 70 years of age 43…”
Section: Management Of Muscle Invasive Bladder Cancer In the Elderlymentioning
confidence: 72%
“…A single-institution case series demonstrated similar rates of eligibility for definitive local therapy following cisplatin-based NAC. Additionally, it reported similar clinical outcomes including pathologic CR, overall survival, and relapse-free survival at 3 years in patients aged ≥70 years versus younger patients with MIBC 42. A recent study of tolerability and efficacy of cisplatin-based combination chemotherapy in metastatic disease based on data from eight Phase II and III clinical trials with a total of 543 patients demonstrated no significant differences in the frequency of renal failure (grade 3–4), febrile neutropenia, or treatment-related death or median survival (12.1 months versus 12.8 months; P =0.91) for patients older and younger than 70 years of age 43…”
Section: Management Of Muscle Invasive Bladder Cancer In the Elderlymentioning
confidence: 72%
“…In our study patient's age was significantly associated with response, as younger patients (≤60 years) responded better than older (>60 years) patients. Other researchers didn't find a significant difference between younger and older patients and concluded that any fit patient of any age group can benefit from the treatment 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Their findings should be transferrable to many other countries and health systems (O'Donovan et al 2015). Chau et al (2015) and Qiu et al (2015) both conducted traditional clinical trials comparing younger and older patients. The latter study looks at differences in clinicopathological features and prognosis of triple-negative breast cancer (TNBC) between younger (<60 years old) and elderly (≥60 years old) patients.…”
mentioning
confidence: 99%
“…Chau et al . () and Qiu et al . () both conducted traditional clinical trials comparing younger and older patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation